Location services and technologies of 5G-Advanced network - Ming AI; Yunjing HOU; Runze ZHOU; Mao CAI (Dianxin kexue)
The Release15 (Rel-15) of the 5G standard developed by 3GPP only supports the location service requirements of emergency services.The standardization of 5G location service network architecture, network element functions, end-to-end process design, positioning reference signals, measurement quantities, measurement processes, etc, has been completed in Rel-16, which is the complete version of location services that supporting business scenarios.In Rel-17, further reduction of the location service delay and improving the positioning accuracy are achieved.The 3GPP will start Rel-18 location service and positioning study in 2022, which mainly includes further improving positioning performance index, such as lower delay, and lower power and higher accuracy positioning, and further expanding positioning functions, such as supporting sidelink positioning, user plane positioning and UE (user equipment) location verification optimization of satellite access scenarios.Based on the introduction of the status of Rel-15/Rel-16/Rel-17 location services, some potential key technologies for realizing Rel-18 location services were put forward and analyzed.Then, the summary that the positioning requirements of 6G network are higher accuracy support the positioning of higher speed scenarios and support more vertical industries and scenarios was pointed out.Artificial intelligence and terahertz communication will become potential key technologies to realize 6G higher accuracy location services.